Financial Sector Assessment Program : Montenegro Corporate Sector Financial Reporting - World Bank (World Bank, Washington, DC, 2016)
This note is prepared as part of the FSAP. Its main objective is to describe the status and recent developments in corporate financial reporting framework in Montenegro and highlight key issues relevant to financial sector. The note represents a technical annex to the main FSAP Aide-Memoire and seeks to provide a high level overview of developments since the 2007 A&A ROSC2, as well as highlight the areas that are most relevant to the financial sector. The Annex 1 to this note offers details on status of implementation of 2007 A&A ROSC policy recommendations and was based on the team’s knowledge of corporate financial reporting reforms in Montenegro and limited research. Montenegro has undertaken notable efforts to improve the corporate financial reporting framework since the 2007 A&A ROSC, especially in improving the statutory framework and efforts to align it with the EU acquis communautaire. However, implementation and enforcement of financial reporting and auditing requirements has been hampered by major capacity and resource constraints. The major consequences are that, with exception of banks and insurance companies, there is limited quality financial information on corporate entities available in the market that is reliable for economic decision making or supervision of financial sector entities. The capacity and skills of the accounting and auditing profession in Montenegro needs further development while the institutions responsible for accounting and auditing regulation, in some cases, are at inception. acquis communautaire.